Electric pulse disintegration of rocks and ores - russian experience; XXVI International Mineral Processing Congress (IMPC) 2012, New Delhi, India, 24-28 September 2012 : Conference Proceedings - Usov A. F.; Tsukerman V. A.; Kurets (Kuretz) V. I. Valery Isaakovich; Potokin A. С. (2012, 2012)
The studies carried out by the Russian researchers and those carried out jointly within some contracts with scientific organizations and companies of other countries, show that the electric pulse disintegration of materials (ED), proposed and investigated in detail in Russia (Kalyatsky, et al, 1980; Usov et al, 1987; Semkin et al, 1995; Usov and Tsukerman, 2000; Kurets et al, 2002) has been widely recognized and developed abroad (Andres, 1995; Inoue et al, 2000; Biela et al, 2008). The Russian and international journals and the proceedings of the conferences dealing with the electric pulse disintegration pay great attention to the principal principals of selective disintegration of materials. There is no, however, any information concerning both the technical means developed to implement the technique and the assessment of their performance, which would be necessary in objective assessment of the industrial use of the technology. The results of long-term studies of the technique and technologies of electric pulse disaggregation by research institutes such as Research Institute of High Voltages (Tomsk), Kola Science Centre of RAS (Apatity), Institute "Mekhanobr"(S.Pertersburg) described. Exploratory stands and technological installations are developed to carry out pilot tests and operations under production conditions. Basic circuits and classification of technical means electric pulse disintegration of the materials are proposed, the analysis of transportation schemes and classification of the material in the disintegration apparatus are given, construction of chambers for continuous stadial disintegration of ores and materials are presented. The features and technological efficiency of electric pulse disintegration of various types of ores, and the spheres of effective use of the method have been determined. Keywords: electropulse disintegration, disintegration machines, chambers of comminution, stadial comminution.